2021
DOI: 10.1037/mot0000195
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of the relationships between students’ internalized symptoms and achievement goals.

Abstract: Previous research revealed that internalized symptoms of depression and anxiety are associated with adolescents' academic motivation. However, a gap remains regarding the longitudinal relationships between students internalized symptoms and their motivational functioning. Using achievement goals to conceptualize motivational functioning, this study examined the longitudinal relationships between adolescents' trajectories of achievement goals and their symptoms of depression and anxiety over a 6-year period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…Results suggested that symptoms of distress at baseline did not affect dropout, which could be a result of the brevity of SSIs. Loss of motivation is associated with internalizing symptoms, which suggests lengthier interventions may be more difficult for individuals with high internalizing symptoms to complete ( Madjar et al, 2021 ). Intentionally brief interventions may reduce this barrier and equalize completion rates for individuals with higher symptoms and lower symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggested that symptoms of distress at baseline did not affect dropout, which could be a result of the brevity of SSIs. Loss of motivation is associated with internalizing symptoms, which suggests lengthier interventions may be more difficult for individuals with high internalizing symptoms to complete ( Madjar et al, 2021 ). Intentionally brief interventions may reduce this barrier and equalize completion rates for individuals with higher symptoms and lower symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, performance-avoidance goals seem to be even more damaging to youth's mental health DEPRESSIVE SYMPTOMS AND SCHOOL FUNCTIONING than performance-approach goals (Ellis et al, 2019;Masselink et al, 2018;Miller & Markman, 2007;Rudolph et al, 2018;Sherratt & MacLeod, 2013;Sideridis, 2005;Winch et al, 2015). Likewise, students pursuing mastery goals in general tend to display a better adjustment and fewer depressive symptoms than their peers pursuing performance (approach or avoidance) goals (Madjar et al, 2021). Unfortunately, the distinction between masteryintrinsic and mastery-extrinsic goals has not yet been investigated in relation to youth's depression trajectories.…”
Section: Youth's Achievement Goals As a Predictor Of Depressive Symptomsmentioning
confidence: 99%
“…This may also be a result of the brevity of SSIs. Loss of motivation is associated with internalizing symptoms, which suggests lengthier interventions may be more difficult for individuals with high internalizing symptoms to complete (Madjar et al, 2021). Intentionally brief interventions may reduce this barrier and equalize completion rates for individuals with higher symptoms and lower symptoms.…”
Section: Discussionmentioning
confidence: 99%